Takaful (Islamic insurance) benefit: ownership and distribution issues in Malaysia - Mohd Noor, Azman; Abdullah, Mohamad Asmadi (Islami Bank Training and Research Academy, 2009)
This paper aims at investigating the ownership of the Takaful benefit and the issues of hibah in nomination. The focus is made solely on the Family takāful because this type of policy is singularly related to death. In this regard, the question is raised as whether the money paid by the takāful operator on the death of the participant (death benefit) before the policy matures constitutes the participant’s estate or not, and secondly over the validity of making a conditional hibah of that takaful policy to a nominee as a sole beneficiary